2009
DOI: 10.4025/actascianimsci.v31i3.6014
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento ingestivo de cordeiros em três sistemas de produção em pastagem de Tifton 85

Abstract: RESUMO.O objetivo deste estudo foi avaliar o comportamento ingestivo de cordeiros em pastagem de Tifton-85 (Cynodon spp.) em três sistemas de produção: cordeiros desmamados aos 60 dias de idade e mantidos em pastagem; cordeiros mantidos com suas mães em pastagem; e cordeiros mantidos com suas mães em pastagem e suplementados em creep feeding. O delineamento foi em blocos ao acaso com três repetições, utilizando quatro cordeiros-teste por repetição. Na pastagem, avaliou-se a altura, a massa, a composição morfol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
1
2
0
1
Order By: Relevance
“…In studies with sheep on bermudagrass pasture, Poli et al (40) found that grazing was the activity that took up most of the lambs' time in the three production systems (lambs weaned on pasture; unweaned lambs exclusively on pasture; and unweaned lambs supplemented on pasture), consistent with results from the present study.…”
Section: Behavior Throughout the Daysupporting
confidence: 90%
“…In studies with sheep on bermudagrass pasture, Poli et al (40) found that grazing was the activity that took up most of the lambs' time in the three production systems (lambs weaned on pasture; unweaned lambs exclusively on pasture; and unweaned lambs supplemented on pasture), consistent with results from the present study.…”
Section: Behavior Throughout the Daysupporting
confidence: 90%
“…The time for rumination is related to the nature of the diet, being proportional to the cell wall content of the bulky ones. Thus, the higher the fiber content in the diet, the longer the time spent in rumination (Van Soest, 1994, Poli et al 2009.…”
Section: Ingestive Behaviormentioning
confidence: 99%
“…Despite this, the production of lambs on pastures with high productivity is challenging and some studies indicate unsatisfactory performance of the animals, below 100 g/day [1416]. The productivity of lambs on pasture is attributed to their ability to harvest nutrients efficiently and effectively from the pasture [17], and the understanding of ingestive behavior is an important tool for directing management practices to obtain better animal performance. Therefore, before making adjustments to tropical pasture management to improve animal performance, it is essential to understand the dynamics of ingestive behavior of these animals.…”
Section: Introductionmentioning
confidence: 99%